From Blood to Therapy: The Revolutionary Application of Platelets in Cancer-Targeted Drug Delivery - Lijuan Xie; Fengxu Gan; Yun Hu; Yibin Zheng; Junshan Lan; Yuting Liu; Xiaofang Zhou; Jianyu Zheng; Xing Zhou; Jie Lou (Journal of Functional Biomaterials)
Biomimetic nanodrug delivery systems based on cell membranes have emerged as a promising approach for targeted cancer therapy due to their biocompatibility and low immunogenicity. Among them, platelet-mediated systems are particularly noteworthy for their innate tumor-homing and cancer cell interaction capabilities. These systems utilize nanoparticles shielded and directed by platelet membrane coatings for efficient drug delivery. This review highlights the role of platelets in cancer therapy, summarizes the advancements in platelet-based drug delivery systems, and discusses their integration with other cancer treatments. Additionally, it addresses the limitations and challenges of platelet-mediated drug delivery, offering insights into future developments in this innovative field.